The places we've been : field reports from travelers under 35 - Brisebois, Asha Veal (Chicago : The Places We've Been Books, 2013)
"The Places We've Been: Field Reports from Travelers Under 35 offers a peer-written collection of 48 vivid and transportive, personal and original nonfiction pieces that portray contemporary snapshots across the globe."--Cover.
Keywords: Travelers' writings; Travel -- Anecdotes; Travelers -- Anecdotes; Voyages and travels -- Anecdotes; Travel; Travelers; Travelers' writings; Voyages and travels; Anecdotes; Anecdotes